Enseñabilidad. La necesidad de una revision crítica en contabilidad (2016)
This paper has as main concern the conceptual discussion regarding the teachability in accounting from a critical review, i.e., the need to understand the particular forms on which accounting is taught, so that it contributes to the improvement of educational accounting practices. The procedural methodology presented refers a provocation to critical thinking; a conceptual discussion regarding teachability, seen through accounting. A praxeological proposal from the otherness that intends to reveal the importance of a teachable and understandable accounting, in addition to ethical and human. The research results are summarized in the obligation to understand the ways in which is taught in the Public Accounting programs in Colombia, it makes explicit the relevance of social and humanistic relation with accounting as an enhancing connection in the comprehensive formation of individuals. Finally, different teachability alternatives are presented which focus the understating of the accounting tasks in the solution of social problems.